Determinación del tipo de estimulación óptima por categoría de pozo mediante la realización de un análisis multivariable y la cuantificación de su impacto a través de análisis nodal en un campo en la cuenca de los Llanos Orientales, operado por Hocol S.A. (2020)
The operator company HOCOL S.A. was required to investigate the wells located in the Eastern Llanos Basin due to the low production performance obtained after stimulation works since 2009. For that reason, it was gathered information about the wells as the result of the stimulations. Subsequently, this study was arose aiming to generate a tool to optimise the selection of stimulation processes and ensure their profit. In order to enable the complete of this study, it is necessary to analyse the different types of stimulation, to comprehend how the wells were intervened and the result of the performance before and after the stimulations. Therefore, the wells are divided in groups in accordance with petro physic properties and similarities in reservoir, production and completion characteristics. This will allow identification and assessment of the stimulation treatment and, eventually, will enable diagnosis of the right type of stimulation for each group.